ERROR ANALYSIS OF INFLECTIONAL AFFIXATION IN ACADEMIC WRITING OF FRESHMAN STUDENTS - Florianus, Clauvico Chesario; Syamsi, Vera (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
Errors, defined as mistaken application of linguistic theory done by language learners, are generally seen as negative element in language learning. However, several researchers believed that error analysis can be used to understand how students process a target language. Understanding this will give insights on which areas of language the students find it difficult. Therefore, this study was conducted for this purpose. Descriptive qualitative methodology was employed to examine types of writing errors that are related to inflectional affixation performed by 8 freshman students. The errors that were identified in the students’ written language were described in linguistic and surface category. Authoritative interpretation was conducted to investigate the cause of error occurrence through interview. The study finds that the students still face difficulty in subject-verb agreement, plurals, and past participle. Furthermore, it was also found that the dominant cause of the error occurrence is interlingual factors, negative transfer from their first language.